1962
DOI: 10.1111/j.1476-5381.1962.tb01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Chemotherapy of Ampicillin—a New Broad‐spectrum Penicillin

Abstract: The pharmacology and chemotherapy of a new penicillin, 6[D(-)-a-aminophenylacetamido] penicillanic acid, are described. It is non-toxic, is absorbed orally and is distributed throughout the body in a manner similar to other penicillins. It is eliminated unchanged from the body in high concentrations in the bile and urine. Almost all of the antibiotic can be accounted for in the urine and intestinal contents 2 hr after intramuscular administration but not after oral administration. It is concluded that the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
2

Year Published

1965
1965
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 3 publications
(2 reference statements)
1
41
1
2
Order By: Relevance
“…The extent of this tubular transport is small, especially when compared with the marked secretion of benzylpenicillin and methicillin (Acred, Brown, Turner & Wright, 1961) and ampicillin (Acred, Brown, Turner & Wilson, 1962). The results with cephaloridine are closely similar to those obtained with cloxacillin by Acred & Brown (1963), who observed that the percentage excretion after a 100-mg dose was only 5.8% greater on the injected side during the first hour after administration and that thereafter there was no difference in the percentage excreted by the two kidneys.…”
Section: Discussionsupporting
confidence: 82%
“…The extent of this tubular transport is small, especially when compared with the marked secretion of benzylpenicillin and methicillin (Acred, Brown, Turner & Wright, 1961) and ampicillin (Acred, Brown, Turner & Wilson, 1962). The results with cephaloridine are closely similar to those obtained with cloxacillin by Acred & Brown (1963), who observed that the percentage excretion after a 100-mg dose was only 5.8% greater on the injected side during the first hour after administration and that thereafter there was no difference in the percentage excreted by the two kidneys.…”
Section: Discussionsupporting
confidence: 82%
“…The rat tissue distribution experiments showed that the pattern of distribution of ticarcillin and clavulanic acid was similar to that after administration of the two compounds in the ratio of 15:1 (10) and was not unlike that seen for other ,B-lactam compounds in rats (1). The concentrations in tissues generally depended upon vascularity and whether excretory processes were present.…”
Section: Discussionmentioning
confidence: 94%
“…The antifungal activity was tested using the pathogenic yeast strain Candida albicans (ATCC 10231) and Aspergillus niger (ATCC 16404). DMSO was used as a solvent control and the standard drugs used were Ampicillin 23 and Griseofulvin…”
Section: Procedures For Anti-microbial Activitymentioning
confidence: 99%